2011
DOI: 10.14430/arctic4097
|View full text |Cite
|
Sign up to set email alerts
|

Connections between River Runoff and Limnological Conditions in Adjacent High Arctic Lakes: Cape Bounty, Melville Island, Nunavut

Abstract: Hydrological and hydrochemical monitoring of paired watersheds in the High Arctic was conducted in 2003-04 to investigate the influence of seasonal runoff on lake water chemistry and productivity. Despite similar limnological conditions overall between the two lakes, marked differences in aquatic productivity were attributed to watershed and basin morphology and the resultant influences on lake ice deterioration and growing season length. A switch from allochthonous to autochthonous sources of carbon late in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The mean abundance of diatom taxa from all three sites is shown and the error bars depict the standard deviation for the three sites c of periphytic diatoms did differ with length of accrual time on the artificial substrates, despite relatively small changes in water chemistry conditions over the course of the ice-free season in all sites. Although one may expect periphytic diatoms to vary with limnological variables, our results highlight the effect of seasonal changes and draw attention to the fact that measured water chemistry parameters alone cannot Table 3 explain the seasonal changes observed in the periphytic diatoms, similar to findings in other Arctic lakes (Michelutti et al, 2007;Stewart & Lamoureux, 2011). Successional trends in microhabitat colonization likely had an effect on the diatom abundance and community composition identified for the different accrual time periods in this study.…”
Section: Discussionsupporting
confidence: 71%
“…The mean abundance of diatom taxa from all three sites is shown and the error bars depict the standard deviation for the three sites c of periphytic diatoms did differ with length of accrual time on the artificial substrates, despite relatively small changes in water chemistry conditions over the course of the ice-free season in all sites. Although one may expect periphytic diatoms to vary with limnological variables, our results highlight the effect of seasonal changes and draw attention to the fact that measured water chemistry parameters alone cannot Table 3 explain the seasonal changes observed in the periphytic diatoms, similar to findings in other Arctic lakes (Michelutti et al, 2007;Stewart & Lamoureux, 2011). Successional trends in microhabitat colonization likely had an effect on the diatom abundance and community composition identified for the different accrual time periods in this study.…”
Section: Discussionsupporting
confidence: 71%
“…Silicon was not included in TDS because previous research has shown ion concentrations to not be significant in Cape Bounty surface waters (mean concentration of 43.8 µg L −1 in West River measured in 2004) (Stewart and Lamoureux 2011). Daily TDS fluxes were calculated by multiplying sample solute concentrations (or mean concentrations by daily mean discharge).…”
Section: Methodsmentioning
confidence: 99%
“…1). As part of a long-term research program (the Cape Bounty Arctic Watershed Observatory), hydrological, limnological, and sedimentary processes have been investigated and monitored in two adjacent lakes and watershed systems since 2003 (Lamoureux et al 2006;Cockburn and Lamoureux 2008a, b;Dugan et al 2009;McDonald and Lamoureux 2009;Laurin 2010;Pautler et al 2010;Lewis et al 2011;Stewart and Lamoureux 2011). The East and West lakes (unofficial names) have similar morphologies: both are *1.5 km 2 , and maximum depths are 30 and 34 m, respectively.…”
Section: Study Sitementioning
confidence: 99%